Mental Health Self-Movement through Group Activity Therapy to Improve Self-Leadership in People with Mental Disorders - Sitti Sulaihah; M. Suhron; Faisal Amir; Atik Puji Rahayu (Universitas STRADA Indonesia, 2026)
Background: Decreased self-leadership in individuals with mental disorders is a common consequence of psychological impairment and requires serious attention. A preliminary study conducted at Mental Health Center in Bangkalan revealed reduced motivation, limited communication skills, and difficulties in establishing social relationships among patients. Purpose: This study aimed to analyze differences in self-leadership among patients before and after receiving Group Activity Therapy. Methods: This study employed a pre-test–post-test experimental design with a control group. The population consisted of individuals with mental disorders, with a total sample of 34 participants, divided into a control group (n = 17) and an intervention group (n = 17), selected using purposive sampling. The independent variable was Group Activity Therapy, while the dependent variable was self-leadership. Data were collected using a self-leadership observation sheet. Statistical analysis was conducted using the Paired t-test and Mann–Whitney test with a significance level of α = 0.05. Results: The intervention group showed a significant improvement in self-leadership (p < 0.001), while the control group also demonstrated a smaller but significant change (p = 0.041). A significant difference between groups was found (p < 0.001), indicating that Group Activity Therapy had a positive effect on improving self-leadership. Conclusion: Group Activity Therapy is effective in enhancing self-leadership among individuals with mental disorders. Continuous implementation of this therapy is recommended to support recovery and improve patient outcomes.